PRESSURE EFFECT ON TI- OR P-RICH ACCESSORY MINERAL SATURATION IN EVOLVED GRANITIC MELTS WITH DIFFERING K2O/NA2O RATIOS - Green T.H.; Adam J. (My University, 2002)
The solubility of Ti- and P-rich accessory minerals has been examined as a function of pressure and K2O/Na2O ratio in two series of highly evolved silicate systems. These systems correspond to (a) alkaline, varying from alkaline to peralkaline with increasing K2O/Na2O ratio; and (b) strongly metaluminous (essentially trondhjemitic at the lowest K2O/Na2O ratio) and remaining metaluminous with increasing K2O/Na2O ratio (to 3). The experiments were conducted at a fixed temperature of 1000 °C, with water contents varying from 5 wt.% at low pressure (0.5 GPa), increasing through 5-10 wt.% at 1.5-2.5 GPa to 10 wt.% at 3.5 GPa. Pressure was extended outside the normal crustal range, so that the results may also be applied to derivation of hydrous silicic melts from subducted oceanic crust.For the alkaline composition series, the TiO2 content of the melt at Ti-rich mineral saturation decreases with increasing pressure but is unchanged with increasing K content (at fixed pressure). The P2O5 content of the alkaline melts at apatite saturation increases with increased pressure at 3.5 GPa only, but decreases with increasing K content (and peralkalinity). For the metaluminous composition series (termed as ''trondhjemite-based series'' (T series)), the TiO2 content of the melt at Ti-rich mineral saturation decreases with increasing pressure and with increasing K content (at fixed pressure). The P2O5 content of the T series melts at apatite saturation is unchanged with increasing pressure, but decreases with increasing K content. The contrasting results for P and Ti saturation levels, as a function of pressure in both compositions, point to contrasting behaviour of Ti and P in the structure of evolved silicate melts. Ti content at Ti-rich mineral saturation is lower in the alkaline compared with the T series at 0.5 GPa, but is similar at higher pressures, whereas P content at apatite saturation is lower in the T series at all pressures studied. The results have application to A-type granite suites that are alkaline to peralkaline, and to I-type metaluminous suites that frequently exhibit differing K2O/Na2O ratios from one suite to another.
Keywords: GRANITES; ACCESSORY MINERALS; APATITE; RUTILE; SILICATE LIQUID STRUCTURE; FRACTIONATION